Concreto com adição de cinza de bagaço de cana-de-açúcar - Fernandes, Sérgio Eduardo [UNESP] (2014)
The high performance concrete (CAD) has a dense microstructure which provides the same, high strength and reduced permeability. With this, it has high durability, being greater than that of conventional concrete. This fact makes their use is growing rapidly in several works. Regarding bagasse ash cane sugar (CBC), this has great potential to be used as a mineral additive for concrete, since it is composed of silicon dioxide. Thus, this research has the purpose of analyzing the performance of the addition of CBC without undergoing milling, manufacturing of high performance concrete. Replacement of was which is substituted in the proportion of 5%, 10%, 15% and 20%, the amount of aggregate in massa. Os tests were performed: absorption, modulus of elasticity, compressive strength and tensile strength by diametrical compression to the ages of 7, 28, 60 and 90 days. Was reached, so the conclusion that CAD with CBC replacement in 20% of aggregate mass, was what had the best performance, so it was chosen for durability testing trait and which were the following: resistance to chemical attack, wicking, across the penetration of chlorides abrasion test / erosion and water permeability. The results obtained in the tests were compared to tests performed with the same reference concrete, that is, without addition CAD, showing in some cases, the addition of CAD with CBC showed equal or even superior results to the reference concrete